Resin composition, coating agent, separator, and method for producing separator

By combining the urea resin containing hydrogenated polyester-based alcohol with ceramic particles, the problem of poor adhesion of traditional ceramic coating is solved, and excellent adhesion between the ceramic coating and the polyester substrate is achieved, and the heat resistance and mechanical strength of the isolator are improved.

JP2025047375APending Publication Date: 2025-04-03TOSOH CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023155834
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-21
Publication Date
2025-04-03

Smart Images

  • Figure 2025047375000002
    Figure 2025047375000002
  • Figure 2025047375000003
    Figure 2025047375000003
  • Figure 2025047375000004
    Figure 2025047375000004
Patent Text Reader

Abstract

To provide a coating agent that forms a coating layer exhibiting superior adhesion to a polyolefin substrate, and a resin composition used for the coating agent.SOLUTION: A resin composition is disclosed, which contains a urethane resin and ceramic particles, wherein the urethane resin contains a hydrogenated polyolefin polyol as a polyol unit, where the urethane group concentration of the urethane resin is 0.80 to 1.10 mol / kg and the weight-average molecular weight of the urethane resin is in the range of 12,300 to 42,000.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a resin composition, a coating agent, a separator, and a method for producing a separator. [Background technology]

[0002] Separators are the main components of lithium-ion batteries. The main purpose of separators is to prevent short circuits caused by contact between electrodes without impeding the movement of ions between the electrodes. Polyolefin separators made of polyolefin resins are commonly used as separators.

[0003] Polyolefin separators are sometimes treated with a coating agent for the purpose of improving mechanical strength, heat resistance, etc. For example, Patent Document 1 discloses a method for producing a separator for an electrochemical cell by at least partially applying an aqueous dispersion of vinylidene fluoride polymer to at least a part of a substrate.

[0004] The above-mentioned Patent Document 1 discloses that an inorganic filler may be used to improve the thermal stability of the separator, and gives ceramic particles as an example of the inorganic filler. A separator treated with a coating agent containing such ceramic particles is called a ceramic-coated separator (CCS) or the like, and has attracted attention as a separator for lithium-ion batteries in particular due to its high thermal stability. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Special Publication No. 2021-533544 [Non-patent literature]

[0006] [Non-Patent Document 1] Owens, DKJAppl.Polym.Sci.1969,13,1741-1747. [Non-Patent Document 2] Lee, H., Alcoutlabi, M., Watson, JV, Zhang, XJAppl.Polym.Sci.2013,129,1939-1951. Summary of the Invention [Problem to be solved by the invention]

[0007] In order to maintain the effect of the ceramic coating, it is important to suppress peeling of the coating layer from the substrate and to prevent the substrate surface from being exposed. However, since the surface of a polyolefin substrate is difficult to wet and generally shows poor adhesion to resins, conventional ceramic-coated separators using a polyolefin substrate have a problem with adhesion between the coating layer and the substrate.

[0008] In view of the above, some aspects of the present disclosure aim to provide a coating agent that forms a coating layer exhibiting excellent adhesion to a polyolefin substrate and a resin composition used in the coating agent. In addition, some other aspects of the present disclosure aim to provide a separator including a coating layer formed from the coating agent and a method for producing the separator. [Means for solving the problem]

[0009] Some aspects of the present disclosure provide the following [1] to

[14] .

[0010] [1] Contains a urethane resin and ceramic particles, The urethane resin contains a hydrogenated polyolefin polyol as a polyol unit, The urethane resin has a urethane group concentration of 0.80 to 1.10 mol / kg; The resin composition, wherein the urethane resin has a weight average molecular weight of 12,300 to 42,000.

[0011] [2] The resin composition according to [1], wherein the hydrogenated polyolefin polyol contains hydrogenated polybutadiene polyol.

[0012] [3] The hydrogenated polyolefin polyol comprises a hydrogenated polybutadiene polyol, The resin composition according to [1] or [2], wherein the hydrogenated polybutadiene polyol has a molar ratio of 1,2-adduct to 1,4-adduct of 20:80 to 90:10.

[0013] [4] The resin composition according to any one of [1] to [3], wherein the hydrogenated polyolefin polyol has an iodine value of 50 g / 100 g or less.

[0014] [5] The resin composition according to any one of [1] to [4], wherein the hydrogenated polyolefin polyol has a hydroxyl group content of 0.50 to 2.00 mol / kg.

[0015] [6] The resin composition according to any one of [1] to [5], wherein the content of polyol units is 75.0 to 99.9 mass % based on the total mass of the polyurethane.

[0016] [7] The resin composition according to any one of [1] to [6], wherein the urethane resin has a molecular weight distribution index of 2.5 to 6.0.

[0017] [8] The surface energy of the urethane resin is 23 mJ / m 2 The resin composition according to any one of [1] to [7] below.

[0018] [9] The resin composition according to any one of [1] to [8], wherein the content of the urethane resin is 0.50 to 15 parts by mass with respect to 100 parts by mass of the ceramic particles.

[0019]

[10] The resin composition according to any one of [1] to [9], wherein the ceramic particles contain aluminum oxide.

[0020]

[11] A coating agent comprising the resin composition according to any one of [1] to

[10] .

[0021]

[12] The coating agent according to

[11] , which is used in the production of a separator for a lithium ion battery.

[0022]

[13] A polyolefin substrate and a coating layer provided on a surface of the polyolefin substrate, The coating layer contains a urethane resin and ceramic particles, The urethane resin contains a hydrogenated polyolefin polyol as a polyol unit, The urethane resin has a urethane group concentration of 0.80 to 1.10 mol / kg; The lithium ion battery separator, wherein the urethane resin has a weight average molecular weight of 12,300 to 42,000.

[0023]

[14] A method for producing a lithium ion battery separator, comprising: applying the coating agent according to

[11] onto a polyolefin substrate; and heating the applied coating agent to form a coating layer. Effect of the Invention

[0024] According to some aspects of the present disclosure, it is possible to provide a coating agent that forms a coating layer that exhibits excellent adhesion to a polyolefin substrate and a resin composition used in the coating agent. Also, according to some other aspects of the present disclosure, it is possible to provide a separator including a coating layer formed from the coating agent and a method for producing the separator. [Brief description of the drawings]

[0025] [Figure 1] 1 is an SEM image of the peeled surface of the ceramic-coated separator observed in Example 1. [Diagram 2] 1 is an SEM image of the peeled surface of the ceramic-coated separator observed in Example 2. [Diagram 3] 1 is an SEM image of the peeled surface of the ceramic-coated separator observed in Example 3. [Figure 4] 1 is an SEM image of the peeled surface of the ceramic-coated separator observed in Example 4. [Diagram 5] 1 is an SEM image of the peeled surface of the ceramic-coated separator observed in Example 5. [Figure 6] 1 is an SEM image of the peeled surface of the ceramic-coated separator observed in Comparative Example 1. [Figure 7] 1 is an SEM image of the peeled surface of the ceramic-coated separator observed in Comparative Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0026] Preferred embodiments of the present disclosure will be described below, however, the present disclosure is not limited to the following embodiments.

[0027] In this specification, the numerical range indicated by "~" indicates a range including the numerical values ​​described before and after "~" as the minimum and maximum values, respectively. In addition, unless specifically stated otherwise, the units of the numerical values ​​described before and after "~" are the same. In addition, in the numerical range described in this specification, the upper limit or lower limit of the numerical range may be replaced with the value shown in the examples. In addition, the upper limit and lower limit values ​​described individually can be arbitrarily combined. In addition, the materials exemplified below may be used alone or in combination of two or more types, unless otherwise specified. When a plurality of substances corresponding to each component are present in the composition, the content of each component in the composition means the total amount of the plurality of substances present in the composition, unless otherwise specified.

[0028] <Resin composition and coating agent> The resin composition of one embodiment contains a urethane resin and ceramic particles. It is a resin made of polyurethane, which is a reaction product of a urethane resin-forming raw material containing a polyol compound and a polyisocyanate compound (for example, a reaction product obtained by reacting a polyol compound with a polyisocyanate compound in the presence of a catalyst), and contains at least a polyol unit and a polyisocyanate unit. Of the two types of constituent units formed by the reaction (polymerization) of the polyol compound and the polyisocyanate compound, the constituent unit derived from the polyol compound is the polyol unit, and the constituent unit derived from the polyisocyanate compound is the polyisocyanate unit.

[0029] The urethane resin (hereinafter referred to as "urethane resin (A)") contained in the resin composition contains hydrogenated polyolefin polyol as a polyol unit. More specifically, the urethane resin (A) is made of a polyurethane (hereinafter referred to as "polyurethane (A)") containing hydrogenated polyolefin polyol as a polyol unit.

[0030] The urethane group concentration of the urethane resin (A) is 0.80 to 1.10 mol / kg, and the weight average molecular weight of the urethane resin (A) is 12300 to 42000. Here, the urethane group concentration of the urethane resin means the number of moles of the urethane group (-NHCOO-) contained per 1 kg of the urethane resin. The same applies to the urethane group concentration of the polyurethane, and means the number of moles of the urethane group (-NHCOO-) contained per 1 kg of the polyurethane. In addition, the urethane group concentration and weight average molecular weight of the urethane resin (A) mean the urethane group concentration and weight average molecular weight of the entire urethane resin (A). That is, the urethane group concentration and weight average molecular weight of the urethane resin (A) mean the urethane group concentration and weight average molecular weight of the polyurethane (A) when the urethane resin (A) is composed of a single polyurethane (A), and mean the urethane group concentration and weight average molecular weight of the mixture when the urethane resin (A) is a mixture of two or more polyurethanes (A). The urethane group concentration and weight average molecular weight of the mixture may be weighted average values ​​based on the blending ratio for the urethane group concentration and weight average molecular weight of each polyurethane contained in the mixture.

[0031] The resin composition can be used as an adhesive, but is preferably used as a coating agent. A coating agent containing the resin composition can form a coating layer that exhibits excellent adhesion to a polyolefin substrate. Therefore, the resin composition (coating agent) is suitable for coating polyolefin substrates, and is preferably used, for example, in the manufacture of lithium ion battery separators. Specifically, a ceramic-coated separator having a coating layer with excellent durability can be obtained by coating the surface of a polyolefin substrate with a coating agent containing the resin composition. The polyolefin substrate referred to here is a substrate that contains at least a polyolefin resin and has a coating surface composed of the polyolefin resin. Examples of polyolefin resins include polyethylene, polypropylene, ethylene propylene rubber, and ethylene propylene diene rubber, and the coating layer exhibits particularly strong adhesion to polyethylene and polypropylene.

[0032] Although the reason why the above effect is obtained is not clear, the present inventors speculate as follows.

[0033] First, the urethane resin (A) has a weight average molecular weight of 12300 to 42000, and therefore has a property of being easily fluidized by heating. In addition, the urethane resin (A) contains hydrogenated polyolefin polyol as a polyol unit, and therefore has a low polarity portion (polyolefin portion derived from hydrogenated polyolefin polyol) and a high polarity portion (urethane bond). Since the urethane group concentration is 0.80 to 1.10 mol / kg, the concentration of the low polarity portion and the high polarity portion is well balanced, and it is considered to have a property of being easily penetrating into the polyolefin substrate (particularly the non-crystalline portion) when fluidized (for example, melted) by heating. Therefore, it is presumed that by applying the resin composition (coating agent) onto the polyolefin substrate and heating it, a bonding region in which the polyolefin resin in the polyolefin substrate and the urethane resin (A) are mixed is formed on the surface of the polyolefin substrate (the interface between the polyolefin substrate and the coating layer), and the polyolefin substrate and the coating layer are firmly bonded to each other.

[0034] By the way, polyolefin substrates generally have low heat resistance and are prone to problems such as deterioration due to heat treatment at high temperatures (e.g., 140°C or higher). On the other hand, as described above, the urethane resin (A) has the property of being easily fluidized by heating, and tends to have sufficient fluidity even at low temperatures (e.g., 130°C or lower). Therefore, according to the above resin composition (coating agent), a coating layer that exhibits excellent adhesion to the polyolefin substrate can be formed without heat treatment at high temperatures. From this perspective, the above resin composition (coating agent) can be said to be suitable for coating polyolefin substrates.

[0035] Hereinafter, each component that may be contained in the resin composition will be described. In the following description, the term "resin composition" may be read as "coating agent."

[0036] (Urethane resin (A)) The polyol unit contains hydrogenated polyolefin polyol. The polyolefin polyol is a compound having a plurality of hydroxyl groups in the main chain or side chain of the polyolefin, and the hydrogenated polyolefin polyol is a hydrogenated product obtained by hydrogenating the polyolefin polyol. The hydrogenated polyolefin polyol contained as the polyol unit in the urethane resin (A) may be one or more kinds. Similarly, the hydrogenated polyolefin polyol contained as the polyol unit in the polyurethane (A) may be one or more kinds.

[0037] The hydrogenated polyolefin polyol may be one in which all double bonds in the polyolefin polyol are hydrogenated, or one in which double bonds in the polyolefin polyol are partially hydrogenated. That is, the polyolefin polyol may have double bonds in its molecular structure. The double bond content in the hydrogenated polyolefin polyol can be confirmed using the iodine value as an index.

[0038] From the viewpoint of further improving the adhesion of the coating layer and the ceramic particles in the coating agent to the substrate (particularly the polyolefin substrate), the iodine value of the hydrogenated polyolefin polyol is preferably 50 g / 100 g or less, more preferably 25 g / 100 g or less, and even more preferably 15 g / 100 g or less. The iodine value of the hydrogenated polyolefin polyol may be 10 g / 100 g or less. The lower limit of the iodine value of the hydrogenated polyolefin polyol is 0 g / 100 g. The iodine value of the hydrogenated polyolefin polyol may be 5 g / 100 g or more. The iodine value can be measured in accordance with the JIS standard (JIS K0070).

[0039] From the viewpoint of polymerization with polyisocyanate, the hydrogenated polyolefin polyol preferably has a hydroxyl group at the molecular end (for example, the end of the main chain). From the viewpoint of further improving the adhesion of the coating layer to the substrate (particularly the polyolefin substrate), the hydroxyl group content in the hydrogenated polyolefin polyol is preferably 0.50 mol / kg or more, more preferably 0.83 mol / kg or more, and even more preferably 1.10 mol / kg or more. From the viewpoint of further improving the adhesion of the coating layer to the substrate (particularly the polyolefin substrate), the hydroxyl group content in the hydrogenated polyolefin polyol is preferably 2.00 mol / kg or less, more preferably 1.50 mol / kg or less, and even more preferably 1.30 mol / kg or less. From these viewpoints, the hydroxyl group content in the hydrogenated polyolefin polyol may be, for example, 0.50 to 2.00 mol / kg, 0.83 to 1.50 mol / kg, or 1.10 to 1.30 mol / kg. The hydroxyl group content in the hydrogenated polyolefin polyol can be measured in accordance with JIS K-1557-1.

[0040] From the viewpoint of further improving the adhesion of the coating layer to the substrate (particularly the polyolefin substrate), the number average molecular weight of the hydrogenated polyolefin polyol is preferably 1000 or more, more preferably 1300 or more, and even more preferably 1500 or more. From the viewpoint of further improving the adhesion of the coating layer to the substrate (particularly the polyolefin substrate), the number average molecular weight of the hydrogenated polyolefin polyol is preferably 4000 or less, more preferably 2400 or less, and even more preferably 1800 or less. From these viewpoints, the number average molecular weight of the hydrogenated polyolefin polyol may be, for example, 1000 to 4000, 1300 to 2400, or 1500 to 1800. The number average molecular weight of the hydrogenated polyolefin polyol is a polystyrene-equivalent value measured using gel permeation chromatography (GPC).

[0041] Specific examples of the hydrogenated polyolefin polyol include hydrogenated polybutadiene polyol, hydrogenated polyfarnesene polyol, hydrogenated polyisoprene polyol, etc. From the viewpoint of making the urethane resin (A) more compatible with the solvent, it is preferable that the hydrogenated polyolefin polyol contains hydrogenated polybutadiene polyol.

[0042] The hydrogenated polybutadiene polyol may contain either one of a 1,2-adduct or a 1,4-adduct, or may contain both of them. Here, the 1,2-adduct refers to a structural unit (wherein the 1- and 2-positions are bonded to other structural units) obtained by 1,2-addition of butadiene among structural units derived from butadiene (including those whose double bonds are hydrogenated), and the 1,4-adduct refers to a structural unit (wherein the 1- and 4-positions are bonded to other structural units) obtained by 1,4-addition of butadiene among structural units derived from butadiene (including those whose double bonds are hydrogenated).

[0043] From the viewpoint of making the urethane resin (A) more compatible with the polyolefin base material, the molar ratio of the 1,2-adduct to the 1,4-adduct in the hydrogenated polyolefin polyol (molar number of 1,2-adduct:molar number of 1,4-adduct) is preferably 20:80 to 90:10, more preferably 65:35 to 90:10, further preferably 80:20 to 90:10, and particularly preferably 80:20 to 85:15.

[0044] The polyurethane (A) may contain a structural unit (polyol unit) derived from a polyol compound other than the hydrogenated polyolefin polyol. For example, the polyurethane (A) may contain a polyol compound generally known as a chain extender as a polyol unit.

[0045] Examples of polyol compounds other than hydrogenated polyolefin polyols include polyether polyols such as polyethylene glycols, polypropylene glycols, and polybutylene glycols; monoglycerides such as caprylic acid monoglyceride, capric acid monoglyceride, lauric acid monoglyceride, stearic acid monoglyceride, and behenic acid monoglyceride; glycols having side chains such as 2-methyl-1,3-propanediol and 3-methyl-1,5-pentanediol; etc. These may be used alone or in combination of two or more kinds.

[0046] The content of the constituent units derived from polyol compounds other than hydrogenated polyolefin polyols may be, for example, 0 to 20% by mass based on the total mass of all polyol units contained in the urethane resin (A). That is, the content of polyol units derived from hydrogenated polyolefin polyols in all polyol units contained in the urethane resin (A) may be 80 to 100% by mass. In this case, if the content of polyol units derived from hydrogenated polyolefin polyols in all polyol units is 80% by mass or more, the urethane resin (A) tends to penetrate more easily into the polyolefin substrate, and the adhesion of the coating layer to the substrate (particularly the polyolefin substrate) tends to be further improved. From the viewpoint of easily obtaining the same effect, the content of polyol units derived from hydrogenated polyolefin polyols in all polyol units may be 90% by mass or more or 95% by mass or more.

[0047] The content of the polyol unit in the urethane resin (A) is preferably 75.0 mass% or more, more preferably 80.0 mass% or more, and even more preferably 85.0 mass% or more, based on the total mass of the urethane resin (A) (i.e., the total mass of the polyurethane (A)), from the viewpoint of further improving the adhesion of the coating layer to the substrate (particularly the polyolefin substrate). The content of the polyol unit in the urethane resin (A) is preferably 99.9 mass% or less, more preferably 95.0 mass% or less, and even more preferably 90.0 mass% or less, based on the total mass of the urethane resin (A) (i.e., the total mass of the polyurethane (A)), from the viewpoint of further improving the adhesion of the coating layer to the substrate (particularly the polyolefin substrate). From these viewpoints, the content of polyol units in the urethane resin (A) may be, for example, 75.0 to 99.9 mass%, 80.0 to 95.0 mass%, or 85.0 to 91.0 mass%, based on the total mass of the urethane resin (A) (i.e., the total mass of the polyurethane (A)).

[0048] The polyisocyanate compound contained as a polyisocyanate unit in the urethane resin (A) (i.e., the polyisocyanate compound contained as a polyisocyanate unit in the polyurethane (A)) may be an aromatic polyisocyanate or a non-aromatic polyisocyanate, or may be a modified product thereof (e.g., an allophanate modified product, a biuret modified product, etc.). The polyisocyanate compound contained as a polyisocyanate unit in the urethane resin (A) may be one type or multiple types. Similarly, the polyisocyanate compound contained as a polyisocyanate unit in the polyurethane (A) may be one type or multiple types.

[0049] The aromatic polyisocyanate is a polyisocyanate having an aromatic skeleton. Examples of the aromatic polyisocyanate include diphenylmethane-4,4'-diisocyanate, diphenylmethane-2,4'-diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 1,5-naphthalene diisocyanate, tolidine diisocyanate, xylylene diisocyanate, 1,3-tetramethylxylylene diisocyanate, and 1,4-tetramethylxylylene diisocyanate.

[0050] The non-aromatic polyisocyanate is a polyisocyanate that does not have an aromatic skeleton (for example, a polyisocyanate that has an aliphatic skeleton). Examples of the non-aromatic polyisocyanate include hexamethylene diisocyanate, isophorone diisocyanate, hydrogenated diphenylmethane-4,4'-diisocyanate, hydrogenated diphenylmethane-2,4'-diisocyanate, hydrogenated xylylene diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, 2,4,4-trimethylhexamethylene diisocyanate, dimer acid diisocyanate, and norbornene diisocyanate.

[0051] From the viewpoint of easily obtaining a coating layer having excellent mechanical strength, the polyisocyanate compound preferably contains an aromatic polyisocyanate, and more preferably contains at least one selected from the group consisting of diphenylmethane-4,4'-diisocyanate, diphenylmethane-2,4'-diisocyanate, 2,4-toluene diisocyanate, and 2,6-toluene diisocyanate. The amount of aromatic polyisocyanate in all polyisocyanate compounds (i.e., the content of polyisocyanateol units derived from aromatic polyisocyanate in all polyisocyanate units contained in urethane resin (A)) may be 80 to 100% by mass, 90 to 100% by mass, or 95 to 100% by mass, from the viewpoint of easily obtaining a coating layer having excellent mechanical strength. From a similar viewpoint, the total amount of diphenylmethane-4,4'-diisocyanate, diphenylmethane-2,4'-diisocyanate, 2,4-toluene diisocyanate and 2,6-toluene diisocyanate in all polyisocyanate compounds may be 80 to 100 mass%, 90 to 100 mass%, or 95 to 100 mass%, and the amount of diphenylmethane-4,4'-diisocyanate in all polyisocyanate compounds may be 80 to 100 mass%, 90 to 100 mass%, or 95 to 100 mass%.

[0052] From the viewpoint of facilitating the production of a coating layer having excellent chemical resistance, the polyisocyanate compound may contain at least one selected from the group consisting of hexamethylene diisocyanate, isophorone diisocyanate, hydrogenated diphenylmethane-4,4'-diisocyanate, and hydrogenated diphenylmethane-2,4'-diisocyanate.

[0053] The isocyanate group content in the polyisocyanate compound is preferably 1.7 mol / kg or more, more preferably 2.4 mol / kg or more, and even more preferably 4.0 mol / kg or more, from the viewpoint of further improving the adhesion of the coating layer to the substrate (particularly the polyolefin substrate). The isocyanate group content in the polyisocyanate compound is preferably 12.0 mol / kg or less, more preferably 11.0 mol / kg or less, and even more preferably 8.0 mol / kg or less, from the viewpoint of further improving the adhesion of the coating layer to the substrate (particularly the polyolefin substrate). From these viewpoints, the isocyanate group content in the polyisocyanate compound may be, for example, 1.7 to 12.0 mol / kg, 2.4 to 11.0 mol / kg, or 4.0 to 8.0 mol / kg. The isocyanate group content in the polyisocyanate compound can be measured in accordance with JIS K1603-1.

[0054] The urethane resin (A) may further contain structural units other than the polyol unit and the isocyanate unit, as long as the object of the present invention is not impaired.

[0055] The urethane group concentration of the urethane resin (A) is 0.80 mol / kg or more, and from the viewpoint of further improving the adhesion of the coating layer to the substrate (particularly the polyolefin substrate), it is preferably 0.85 mol / kg or more, and more preferably 0.90 mol / kg or more. The urethane group concentration of the urethane resin (A) is 1.10 mol / kg or less, and from the viewpoint of further improving the adhesion of the coating layer to the substrate (particularly the polyolefin substrate), it is preferably 1.06 mol / kg or less, and more preferably 0.95 mol / kg or less. From these viewpoints, the urethane group concentration of the urethane resin (A) may be, for example, 0.80 to 1.06 mol / kg or 0.80 to 0.95 mol / kg, or may be 0.85 to 1.10 mol / kg or 0.90 to 1.10 mol / kg. The urethane group concentration of the urethane resin (A) can be measured by the method described in the Examples.

[0056] The urethane resin (A) may have a hydroxyl group. The hydroxyl group concentration (hydroxyl group content) of the urethane resin (A) may be, for example, 0.0010 to 0.32 mol / kg, 0.0060 to 0.30 mol / kg, or 0.010 to 0.29 mol / kg.

[0057] The urethane resin (A) may have an isocyanate group, but from the viewpoint of storage stability, the isocyanate group concentration (isocyanate group content) of the urethane resin (A) is preferably 0 to 0.20 mol / kg, more preferably 0 to 0.10 mol / kg, and even more preferably 0 to 0.050 mol / kg. The isocyanate group concentration of the urethane resin (A) may be 0 mol / kg.

[0058] The weight average molecular weight of the urethane resin (A) is 42000 or less, preferably 37000 or less, and more preferably 25000 or less. The smaller the weight average molecular weight of the urethane resin (A), the lower the heat treatment temperature at which a coating layer that is firmly adhered to the polyolefin substrate can be formed. The weight average molecular weight of the urethane resin (A) is 12300 or more, and may be 12500 or more or 13000 or more. When the weight average molecular weight of the urethane resin (A) is appropriately large, deformation of the coating layer is suppressed, and peeling of the coating layer from the substrate is less likely to occur. From these viewpoints, the weight average molecular weight of the urethane resin (A) may be, for example, 12300 to 42000, 12500 to 37000, or 13000 to 25000. The weight average molecular weight of the urethane resin (A) can be measured by the method described in the Examples.

[0059] The molecular weight distribution index (weight average molecular weight / number average molecular weight) of the urethane resin (A) is preferably 2.5 or more, more preferably 2.8 or more, and even more preferably 3.0 or more, from the viewpoint of further improving the adhesion of the coating layer to the substrate (particularly the polyolefin substrate). The molecular weight distribution index of the urethane resin (A) is preferably 6.0 or less, more preferably 5.5 or less, and even more preferably 5.0 or less, from the viewpoint of further improving the adhesion of the coating layer to the substrate (particularly the polyolefin substrate). From these viewpoints, the molecular weight distribution index of the urethane resin (A) may be, for example, 2.5 to 6.0. The weight average molecular weight and number average molecular weight of the urethane resin (A) are polystyrene equivalent values ​​measured using gel permeation chromatography (GPC), and may be measured by the method described in the Examples.

[0060] The surface energy of the urethane resin (A) is 23 mJ / m 2 Less than (e.g., 15 to 23 mJ / m 2 The urethane resin (A) having such a surface energy has the property of easily spreading on a substrate, so that when a coating layer is formed on a polyolefin substrate, for example, a bonding region where the polyolefin in the substrate and the urethane resin (A) are mixed is easily formed, and the polyolefin substrate and the coating layer are more easily bonded to each other. From the viewpoint of making such an effect more easily obtainable, the surface energy of the urethane resin (A) is preferably 22 mJ / m 2or less. Here, the surface energy of the urethane resin (A) is obtained by forming a film made of the urethane resin (A) and measuring the surface energy of the film by the method described in the Examples. Specifically, the film is formed by preparing a cyclohexanone solution with a concentration of 10% by mass of the urethane resin (A), applying the solution to a polyethylene substrate by an applicator method so that the dry film thickness is about 20 μm, and then heating at 80° C. for 4 hours under reduced pressure in a vacuum dryer (evaporating the solvent in the coating film by drying and smoothing the film surface by thermal aging). The physical structure of the film surface may affect the surface energy, but the above method can form a film with a smooth surface, so that the effect of the physical structure of the film surface can be minimized and the surface energy of the urethane resin (A) itself can be obtained. The surface energy of the urethane resin (A) can be adjusted by setting the urethane group concentration of the urethane resin (A) to 0.80 to 1.10 mol / kg and the weight average molecular weight of the urethane resin (A) to 12300 to 42000, as well as by the type of hydrogenated polyolefin polyol. For example, when the urethane group concentration is relatively high, the surface energy tends to be high.

[0061] From the viewpoint of easily obtaining good tackiness, the glass transition temperature of the urethane resin (A) may be −10° C. or lower, −20° C. or lower, or −28° C. or lower. The glass transition temperature of the urethane resin (A) may be, for example, −10 to −80° C., −20 to −70° C., or −28 to −65° C. The glass transition temperature of the urethane resin (A) can be measured in accordance with JIS K6240.

[0062] The urethane resin (A) can be obtained by reacting a urethane resin-forming raw material containing at least a hydrogenated polyolefin polyol and a polyisocyanate compound. Specifically, for example, a polyol compound containing a hydrogenated polyolefin polyol and a polyisocyanate compound can be mixed and heated in the presence of a catalyst (urethanization catalyst) and a solvent (reaction solvent) to obtain a urethane resin (A) made of polyurethane (A), which is a reaction product of the polyol compound and the polyisocyanate compound. Here, the urethane resin-forming raw material is an aggregate of compounds contained in the structural units of the polyurethane (urethane resin), which is the reaction product. Therefore, the catalyst and the solvent are not included in the urethane resin-forming raw material.

[0063] The content of the polyol compound and the polyisocyanate compound in the urethane resin forming raw material (i.e., the blending amount of the polyol compound and the polyisocyanate compound) is, for example, the total number of moles of hydroxyl groups in the polyol compound (M OH ) and the total number of moles of isocyanate groups in the polyisocyanate compound (M NCO ) and the ratio (M NCO / M OH The ratio (M) may be 0.74 to 0.98. NCO / M OH When the ratio (M) is 0.74 or more, the molecular weight of the urethane resin (A) does not become too small, and the mechanical strength of the coating layer formed using the urethane resin (A) tends to be improved. NCO / M OH When the ratio (M) is 0.98 or less, the molecular weight of the urethane resin (A) does not become too large, and the urethane resin (A) tends to penetrate more easily into the polyolefin substrate. NCO / M OH ) may be 0.75 or more, or 0.78 or more, or may be 0.97 or less, or 0.95 or less.

[0064] The content of hydrogenated polyolefin polyol and polyisocyanate compound in the urethane resin forming raw material (i.e., the blending amount of hydrogenated polyolefin polyol and polyisocyanate compound) is determined based on the total mole number of hydroxyl groups in the hydrogenated polyolefin polyol (M OH ') and the total number of moles of isocyanate groups in the polyisocyanate compound (M NCO ) and the ratio (M NCO / M OH The ratio of the above (M ′) may be 0.74 to 0.98. NCO / M OH When the ratio (M′) is 0.74 or more, the molecular weight of the urethane resin (A) does not become too small, and the mechanical strength of the coating layer formed using the urethane resin (A) tends to be improved. NCO / M OH When the ratio (M′) is 0.98 or less, the molecular weight of the urethane resin (A) does not become too large, and the urethane resin (A) tends to penetrate more easily into the polyolefin substrate. NCO / M OH ') may be 0.75 or more, or 0.78 or more, and may be 0.97 or less, or 0.95 or less.

[0065] Examples of the catalyst include organometallic compounds such as dibutyltin diacetate, dibutyltin dilaurate, and dioctyltin dilaurate; organic amines such as triethylenediamine and triethylamine, and salts thereof; etc. These may be used alone or in combination of two or more.

[0066] The amount of catalyst may be selected according to the reactivity of the polyisocyanate compound used. The amount of catalyst is, for example, preferably 0.00010 parts by mass or more and 25 parts by mass or less per 1 part by mass of urethane resin-forming raw material, more preferably 0.0010 parts by mass or more and 6.0 parts by mass or less, and even more preferably 0.010 parts by mass or more and 1.0 parts by mass or less. If the amount of catalyst is 0.00010 parts by mass or more per 1 part by mass of urethane resin-forming raw material, sufficient catalytic effect is more likely to be obtained. If the amount of catalyst is 25 parts by mass or less per 1 part by mass of urethane resin-forming raw material, it is more preferable in terms of economic efficiency.

[0067] Examples of the solvent include aromatic hydrocarbon solvents such as toluene, ethylbenzene, trimethylbenzene, and xylene; aliphatic hydrocarbon solvents such as pentane, hexane, and cyclohexane; ketone solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; alcohol solvents such as methanol, ethanol, isopropanol, ethylene glycol, diethylene glycol, triethylene glycol, and propylene glycol; glycol ether solvents such as methyl cellosolve, ethyl cellosolve, butyl cellosolve, methyl diglycol, ethyl diglycol, butyl diglycol, and propylene glycol monomethyl ether; ester solvents such as ethyl acetate, butyl acetate, and propylene glycol monomethyl ether acetate; amide solvents such as N,N-dimethylformamide, N,N-diethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone; ether solvents such as diethyl ether and tetrahydrofuran; and water. These may be used alone or in combination of two or more.

[0068] The blending amount of the solvent is not particularly limited, and may be, for example, from 1.0 part by mass to 10,000 parts by mass per 100 parts by mass of the urethane resin-forming raw material.

[0069] The urethane resin (A) may consist of one type of polyurethane (A), or may be a mixture of two or more types of polyurethane (A) differing in the types of constituent units (polyol units, polyisocyanate units, etc.), urethane group concentrations, weight average molecular weights, etc.

[0070] The content of the urethane resin (A) in the resin composition is preferably 0.50 parts by mass or more, and may be 1.0 parts by mass or more or 3.0 parts by mass or more, relative to 100 parts by mass of the ceramic particles, from the viewpoint of further improving the adhesion of the coating layer to the polyolefin substrate. The content of the urethane resin (A) in the resin composition is preferably 15 parts by mass or less, and may be 10 parts by mass or less or 5.0 parts by mass or less, relative to 100 parts by mass of the ceramic particles, from the viewpoint of less inhibiting the movement of electrons in the lithium ion battery. From these viewpoints, the content of the urethane resin (A) in the resin composition is preferably 0.50 to 15 parts by mass relative to 100 parts by mass of the ceramic particles.

[0071] (ceramic particles) Ceramic particles are particles containing ceramics. Examples of ceramics include aluminum oxide (Al 2 O 3 ), boehmite (AlOOH), titanium oxide (TiO 2 ), silicon oxide (SiO 2 ), zinc oxide (ZnO 2 ), metal oxides such as SiO 2 , metal hydroxides, metal carbonates, silicic acid, kaolin, talc, minerals, glass, etc. The ceramic particles may be composed of only one of these materials, or may contain two or more kinds.

[0072] As the ceramic particles, a wide variety of known ceramic particles used in the manufacture of ceramic-coated separators can be used, and the type of ceramic particles can be selected depending on the application and purpose. From the viewpoint of heat resistance, the ceramic particles preferably contain aluminum oxide.

[0073] The ceramic particles may contain materials other than ceramics (metallic materials or organic materials) as long as the function of the ceramic particles is not impaired, but the ceramic content is preferably 95 mass% or more, and more preferably 99 mass% or more.

[0074] The average particle size of the ceramic particles may be, for example, 0.010 to 5.0 μm, 0.10 to 3.0 μm, or 0.40 to 1.0 μm. The average particle size is measured by particle size analysis using a laser diffraction / scattering method in accordance with JIS Z8825.

[0075] From the viewpoint of further enhancing the coating effect (effect of improving the performance such as heat resistance and mechanical strength of the separator), the content of the ceramic particles in the resin composition is preferably 85 mass% or more, and may be 90 mass% or more or 95 mass% or more, based on the total solid content of the resin composition. The content of the ceramic particles in the resin composition is preferably 99.5 mass% or less, and may be 99 mass% or less or 97 mass% or less, based on the total solid content of the resin composition. In this specification, the solid content means components other than the solvent.

[0076] (Other ingredients) The resin composition may further contain components other than the urethane resin (A) and the ceramic particles.

[0077] The resin composition may contain a solvent, for example, for the purpose of adjusting viscosity, etc. Examples of the solvent include N-methyl-2-pyrrolidone and the compounds exemplified as reaction solvents for synthesizing the above-mentioned urethane resin (A).

[0078] The content of the solvent may be selected in consideration of the coating method, the desired film thickness of the coating layer, and the like. The content of the solvent in the resin composition is, for example, preferably 1.0 to 10,000 parts by mass, more preferably 40 to 3,200 parts by mass, and even more preferably 150 to 2,000 parts by mass, relative to 100 parts by mass of the solid content of the resin composition. When the content of the solvent is 1.0 part by mass or more relative to 100 parts by mass of the solid content of the resin composition, the viscosity of the resin composition is reduced and the coatability is improved. When the content of the solvent is 10,000 parts by mass or less relative to 100 parts by mass of the solid content of the resin composition, the film thickness of the coating layer formed is not too thin, and a sufficient film thickness is easily obtained.

[0079] As the other components, for example, a catalyst and the like can also be used.

[0080] The other components may be raw materials capable of forming a urethane resin, such as a polyol compound or a polyisocyanate compound, or may be components used in the synthesis of a urethane resin, such as the above-mentioned urethane-forming catalyst or reaction solvent.

[0081] In the resin composition, the urethane resin (A) can be called a binder resin because it has a function of binding ceramic particles in the resin composition together. The resin composition may contain a binder resin other than the urethane resin (A). When the resin composition further contains a binder resin other than the urethane resin (A), the content of the urethane resin (A) is preferably 80% by mass or more and less than 100% by mass, more preferably 85% by mass or more and less than 100% by mass, and even more preferably 90% by mass or more and less than 100% by mass, based on the total mass of the binder resin contained in the resin composition, from the viewpoint of easily obtaining the above-mentioned effects of the urethane resin (A). Examples of the binder resin other than the urethane resin (A) include urethane resins other than the urethane resin (A), that is, urethane resins made of polyurethane that do not contain hydrogenated polyolefin polyol as a polyol unit.

[0082] <Separator and manufacturing method thereof> The separator of one embodiment is a separator for a lithium ion battery, and includes a polyolefin substrate and a coating layer provided on a surface of the polyolefin substrate. The coating layer contains the urethane resin (A) and the ceramic particles.

[0083] The polyolefin substrate contains a polyolefin resin such as polyethylene, polypropylene, ethylene propylene rubber, ethylene propylene diene rubber, etc. The polyolefin substrate is, for example, a porous or microporous membrane (film or sheet) and has ion conductivity.

[0084] As the polyolefin substrate, a known polyolefin substrate (e.g., a polyolefin separator such as a polyolefin porous membrane) used in the manufacture of a ceramic-coated separator can be used, and the type can be selected depending on the application and purpose. From the viewpoint of superior adhesion to the coating layer, the polyolefin substrate preferably contains at least one of polyethylene and polypropylene.

[0085] The coating layer is strongly adhered to the polyolefin substrate because it contains the urethane resin (A). In the separator, a bonding region where the polyolefin resin in the substrate and the urethane resin (A) in the coating layer are mixed may be formed at the interface between the polyolefin substrate and the coating layer.

[0086] The coating layer may contain other components that may be contained in the resin composition of the above embodiment, but the content of the solvent in the coating layer is preferably 1 mass % or less based on the total mass of the coating layer.

[0087] The thickness of the coating layer is not particularly limited, but is preferably 1 to 50 μm, and may be 2 to 30 μm or 5 to 20 μm. When the thickness of the coating layer is 1 μm or more, the coating layer tends to have better adhesion. When the thickness of the coating layer is 50 μm or less, the time required for drying to form the coating layer can be further reduced, and better productivity can be obtained.

[0088] The method for producing the separator includes, for example, applying a coating agent containing the resin composition of the embodiment onto a polyolefin substrate, and heating the coating agent to form a coating layer.

[0089] The method for applying the coating agent is not particularly limited, and examples thereof include an applicator method, a bar coating method, a spin coating method, a spray coating method, a dip coating method, a nozzle coating method, a gravure coating method, a reverse roll coating method, a die coating method, an air doctor coating method, a blade coating method, a rod coating method, a curtain coating method, a knife coating method, a transfer roll coating method, a squeeze coating method, an impregnation coating method, a kiss coating method, a calendar coating method, an extrusion coating method, and the like.

[0090] The heating may be for drying a film made of a coating agent. The heating temperature (drying temperature) is not particularly limited, but is preferably 130°C or lower from the viewpoint of reducing damage to the polyolefin substrate. The heating temperature is preferably 50°C or higher from the viewpoint of reducing the amount of residual solvent, and may be 70°C or higher or 80°C or higher. The heating time is not particularly limited, but is preferably 1 second to 5 hours from the viewpoint of reducing the amount of residual solvent and reducing the time required for the process. EXAMPLES

[0091] The contents of the present disclosure will be described in more detail below using examples and comparative examples, but the present disclosure is not limited to the following examples.

[0092] <Material preparation> The following materials were prepared. [Hydrogenated polyolefin polyol] Hydrogenated polybutadiene polyol 1: Hydroxyl-terminated hydrogenated polybutadiene (product name: GI-1000, manufactured by Nippon Soda Co., Ltd.), number average molecular weight = 1500, hydroxyl content = 1.22 mol / kg, iodine value = 9.2 g / 100 g, 1,2-adduct:1,4-adduct = 85:15 (molar ratio) Hydrogenated polybutadiene polyol 2: Hydroxyl-terminated hydrogenated polybutadiene (product name: blend of GI-1000 and GI-2000. Both manufactured by Nippon Soda Co., Ltd.), number average molecular weight = 1600, hydroxyl content = 1.15 mol / kg, iodine value = 10.0 g / 100 g, 1,2-adduct:1,4-adduct = 85:15 (molar ratio) Hydrogenated polybutadiene polyol 3: Hydroxyl-terminated hydrogenated polybutadiene (product name: blend of GI-1000 and GI-3000. Both manufactured by Nippon Soda Co., Ltd.), number average molecular weight = 1670, hydroxyl content = 1.15 mol / kg, iodine value = 9.7 g / 100 g, 1,2-adduct:1,4-adduct = 85:15 (molar ratio) Hydrogenated polybutadiene polyol 4: Hydroxyl-terminated hydrogenated polybutadiene (product name: blend of GI-1000 and GI-2000. Both manufactured by Nippon Soda Co., Ltd.), number average molecular weight = 1690, hydroxyl content = 1.08 mol / kg, iodine value = 10.7 g / 100 g, 1,2-adduct:1,4-adduct = 85:15 (molar ratio) Hydrogenated polybutadiene polyol 5: Hydroxyl-terminated hydrogenated polybutadiene (product name: blend of GI-1000 and GI-3000. Both manufactured by Nippon Soda Co., Ltd.), number average molecular weight = 1830, hydroxyl content = 1.08 mol / kg, iodine value = 10.1 g / 100 g, 1,2-adduct:1,4-adduct = 85:15 (molar ratio) [Polyisocyanate] MDI: Diphenylmethane-4,4'-diisocyanate (product name: Millionate MT, manufactured by Tosoh Corporation), isocyanate group content = 7.99 mol / kg [Chain extender] MPD: 2-methyl-1,3-propanediol, manufactured by Tokyo Chemical Industry Co., Ltd. [catalyst] Dioctyltin dilaurate: Kishida Chemical Co., Ltd. [solvent] Cyclohexanone: Fujifilm Wako Pure Chemical Industries, Ltd. N-Methyl-2-pyrrolidone (NMP): Fujifilm Wako Pure Chemical Industries, Ltd. [Ceramic particles] Aluminum oxide particles: (Product name: α-alumina, 0.5 μm. Manufactured by Fujifilm Wako Pure Chemical Industries, average particle size = 0.5 μm) [Binder resin] Polyvinylidene fluoride 1: Sigma-Aldrich, weight average molecular weight = 275,000 Polyvinylidene fluoride 2: Sigma-Aldrich, weight average molecular weight = 530,000

[0093] <Synthesis Example 1> (Preparation of urethane resin composition) A 2L four-necked separable flask equipped with a stirrer, a thermometer, a heating device, and a reflux condenser was charged with 150.0 g of hydrogenated polybutadiene polyol 1, 18.8 g of MDI, 0.137 g of a catalyst (dioctyltin dilaurate), and 1520 g of a solvent (cyclohexanone) at room temperature. Nitrogen gas was then blown into the flask to replace the atmosphere in the flask. The mixture in the flask was reacted for 6 hours under substantially uniform stirring at 80°C to obtain a composition (urethane resin composition) containing a urethane resin (urethane resin (a1)) made of polyurethane (a1).

[0094] (Analysis of urethane resin) The urethane resin composition obtained above was dried under reduced pressure to remove the solvent, and a urethane resin (a1) was extracted, and the urethane group concentration, molecular weight, and other properties of the urethane resin (a1) were measured by the method described below. The results are shown in Table 1. Note that the urethane resin (a1) extracted by this method may contain residual catalyst used in the reaction, but the amount of residual catalyst was extremely small and below the detection limit of the measurement method, so the following measurements were performed assuming that no catalyst remained.

[0095] [Measurement of isocyanate group content and urethane group concentration] First, the isocyanate group content (NCO content) remaining in the urethane resin (a1) after the synthesis reaction was measured in accordance with JIS K1603-1. Next, the nitrogen content in the urethane resin (a1) was measured by elemental analysis. The urethane group concentration in the urethane resin (a1) was calculated from the amount of isocyanate remaining obtained by the measurement and the results of elemental analysis.

[0096] [Measurement of hydroxyl group content] The content of hydroxyl groups (OH content) remaining in the urethane resin (a1) was measured in accordance with JIS K1557-1.

[0097] [Molecular weight measurement] The weight average molecular weight (Mw) and number average molecular weight (Mn) were measured by gel permeation chromatography (GPC) under the following conditions, and the molecular weight distribution index (Mw / Mn) was calculated. The weight average molecular weight and number average molecular weight are polystyrene-equivalent molecular weights. -conditions- Equipment: High-speed GPC equipment (Tosoh HLC-8320GPC) Column: One TSKgel guardcolumn α (6.0mm I.D. x 4cm) and two +α-M (67.8mm I.D. x 30cm) connected in series (all manufactured by Tosoh Corporation). Mobile phase: Cyclohexanone ·Mobile phase speed: 1.0mL / min Column temperature: 40℃ Detector: RI detector (polarity (+)) Sample solution: Cyclohexanone solution (concentration: 1mg / mL) Sample injection volume: 100μL

[0098] [Measurement of glass transition temperature] The glass transition temperature (Tg) of the urethane resin (a1) was measured in accordance with JIS K6240 using differential scanning calorimetry (DSC). The measurement was performed in a nitrogen atmosphere in the temperature range of -80°C to 200°C, with a heating rate of 10°C / min. The gas flow rate was 50mL / min. The sample was sealed in an Al pan.

[0099] (Surface energy measurement) First, the urethane resin composition obtained above was applied to a polyethylene substrate (PE substrate: Kobe Poly Sheet EL-N-AN manufactured by Hitachi Chemical) using an applicator, and after leaving it to stand at room temperature for 5 minutes, it was dried under reduced pressure at 80° C. for 4 hours using a vacuum dryer. As a result, a film (film thickness 20 μm) made of a dried product of the urethane resin composition (urethane resin (a1)) was formed on the PE substrate.

[0100] Next, the contact angles of various probe liquids on the surface of the above film were measured by the sessile drop method in accordance with JIS R3257. 2.0 μL of the probe liquid was dropped, and the contact angle was measured 1 second after dropping using a contact angle measuring device (Kyowa Interface Science Co., Ltd. automatic contact angle meter DMo-601). Two types of probe liquids were used: pure water (72.8 mN / m, Fujifilm Wako Pure Chemical Industries, Ltd.) and diiodomethane (50.8 mN / m, Fujifilm Wako Pure Chemical Industries, Ltd.). The contact angle was measured 10 times for each probe liquid, and the average value was used as the measured value.

[0101] The surface energy of the film was calculated using the contact angle values ​​of pure water and diiodomethane obtained above and Owens' theory (see Non-Patent Document 1), which is a known calculation method.

[0102] <Synthesis Examples 2 to 5> Urethane resin compositions of Synthesis Examples 2 to 5 were prepared in the same manner as Synthesis Example 1, except that the blending amounts of each component were changed as shown in Table 1. The urethane resin compositions of Synthesis Examples 2 to 5 are urethane compositions containing urethane resins composed of polyurethanes (a2) to (a5) (urethane resins (a2) to (a5)). Next, in the same manner as Synthesis Example 1, the urethane resins (a2) to (a5) were each taken out from the obtained urethane resin composition, and the urethane group concentrations, molecular weights, etc. of the urethane resins (a2) to (a5) were measured. Furthermore, in the same manner as Synthesis Example 1, the surface energy of a film (film thickness 20 μm) composed of a dried product of the urethane resin composition (urethane resins (a2) to (a5)) was measured and evaluated.

[0103] <Example 1> 38.8 g of aluminum oxide particles and 49.2 g of a solvent (cyclohexanone) were charged into a 200 mL beaker at room temperature. The mixture in the flask was then dispersed for 10 minutes at room temperature using an ultrasonic disperser. 12 g of a urethane resin composition containing a urethane resin (urethane resin (a1), 1.2 g) made of polyurethane (a1) as a binder was added to the resulting mixture, and the mixture was dispersed for 10 minutes at a rotation speed of 300 rpm using a stirrer equipped with a stirring blade to obtain a coating agent (a resin composition containing a urethane resin and ceramic particles).

[0104] A polyethylene separator (PE separator: SW811G manufactured by Shenzhen Senior Technology Materials Co., Ltd.) was prepared as a polyolefin substrate, and the coating agent obtained above was applied to the polyolefin substrate using an applicator. The obtained laminate was left to stand at room temperature for 5 minutes, and then dried at 80°C for 4 hours using a vacuum dryer to form a coating layer (layer thickness 20 μm) containing the dried product of the coating agent on the PE separator. This resulted in a ceramic-coated separator.

[0105] <Examples 2 to 5> Coating agents containing urethane resin compositions (urethane resins (a2) to (a5)) were prepared in the same manner as in Example 1, except that the amounts of each component were changed as shown in Table 1. Next, ceramic-coated separators were produced in the same manner as in Example 1, except that the coating agents obtained in each Example were used.

[0106] <Comparative Examples 1 to 2> A coating agent containing polyvinylidene fluoride (polyvinylidene fluoride 1 or 2) was prepared in the same manner as in Example 1, except that the blending amount of each component was changed as shown in Table 1. Next, a ceramic-coated separator was produced in the same manner as in Example 1, except that the coating agent obtained in each Comparative Example was used. Polyvinylidene fluoride was dissolved in advance in N-methyl-2-pyrrolidone to a solid content of 5 wt%.

[0107] <Adhesion evaluation> An adhesive tape (Scotch Masking Tape 2899, manufactured by 3M) was applied onto the coating layer of the ceramic-coated separator of Examples 1 to 5 and Comparative Examples 1 and 2 obtained above, and then left to stand at 23°C for 20 hours to obtain a test piece for a T-peel test. The obtained test piece was subjected to a test to peel the adhesive tape from the ceramic-coated separator in accordance with the known T-peel test method described in Non-Patent Document 2. For the test, an Autocom type testing machine (UTPS-Acs(S), manufactured by TSE Corporation) was used.

[0108] Next, the peeled surface of the ceramic-coated separator obtained after the test was observed with a scanning electron microscope (SEM). SEM images observed in Examples 1 to 5 and Comparative Examples 1 and 2 are shown in Figures 1 to 7. The areas on the surface of the ceramic-coated separator where no ceramic particles were present after the test were regarded as areas where the coating layer had peeled off, and the ratio of the area of ​​the peeled off areas (peeled area) to the entire separator surface was calculated, and the adhesion of the coating layer was evaluated according to the following criteria. The results are shown in Table 1. A: No peeling (peeled area is 0% of the entire separator surface) B: Peeling area is more than 0% and less than 10% of the entire separator surface C: Peeling area is 10% or more of the entire separator surface

[0109] [Table 1]

[0110] From the test results of the above adhesion evaluation, it was confirmed that the coating layers of the ceramic-coated separators of Examples 1 to 5 exhibited excellent adhesion to the polyolefin substrate. In the above test, cohesive failure of the coating layers was confirmed in Examples 1 to 5, but the measured peel strength was 0.03 N / 20 mm or more in all Examples (Example 1: 0.03 N / 20 mm, Example 2: 0.05 N / 20 mm, Example 3: 0.03 N / 20 mm, Example 4: 0.08 N / 20 mm, Example 5: 0.13 N / 20 mm), confirming that the coating layers have sufficiently high cohesive strength.

Claims

1. Contains a urethane resin and ceramic particles, The urethane resin contains a hydrogenated polyolefin polyol as a polyol unit, The urethane group concentration of the urethane resin is 0.80 to 1.10 mol / kg; The resin composition, wherein the urethane resin has a weight average molecular weight of 12,300 to 42,000.

2. The resin composition according to claim 1 , wherein the hydrogenated polyolefin polyol comprises a hydrogenated polybutadiene polyol.

3. The hydrogenated polyolefin polyol comprises a hydrogenated polybutadiene polyol, 2. The resin composition according to claim 1, wherein the molar ratio of the 1,2-adduct to the 1,4-adduct in the hydrogenated polybutadiene polyol is from 20:80 to 90:

10.

4. The resin composition according to claim 1, wherein the hydrogenated polyolefin polyol has an iodine value of 50 g / 100 g or less.

5. The resin composition according to claim 1, wherein the hydrogenated polyolefin polyol has a hydroxyl group content of 0.50 to 2.00 mol / kg.

6. The resin composition according to claim 1, wherein the content of the polyol unit is 75.0 to 99.9 mass % based on the total mass of the polyurethane.

7. The resin composition according to claim 1, wherein the molecular weight distribution index of the urethane resin is 2.5 to 6.

0.

8. The surface energy of the urethane resin is 23 mJ / m 2 The resin composition according to claim 1, wherein:

9. The resin composition according to claim 1, wherein the content of the urethane resin is 0.50 to 15 parts by weight based on 100 parts by weight of the ceramic particles.

10. The resin composition of claim 1 , wherein the ceramic particles comprise aluminum oxide.

11. A coating agent comprising the resin composition according to any one of claims 1 to 10.

12. The coating agent according to claim 11, which is used in the manufacture of a separator for a lithium ion battery.

13. A polyolefin substrate and a coating layer provided on a surface of the polyolefin substrate, The coating layer contains a urethane resin and ceramic particles, The urethane resin contains a hydrogenated polyolefin polyol as a polyol unit, The urethane group concentration of the urethane resin is 0.80 to 1.10 mol / kg; The lithium ion battery separator, wherein the urethane resin has a weight average molecular weight of 12,300 to 42,000.

14. A method for producing a lithium ion battery separator, comprising: applying the coating agent according to claim 11 onto a polyolefin substrate; and heating the applied coating agent to form a coating layer.

Citation Information

Patent Citations

  • Battery Separator Coating

    JP2021533544A